Lipitension today — disaster tomorrow: focus on elderly comorbid patients - A. S. Skotnikov; V. D. Zakiev; A. D. Gvozdeva; L. G. Bektemirova (Российский кардиологический журнал)
In elderly and senile patients, a combination of hypertension and atherogenic dyslipidemia is often encountered, which, both separately and in combination ("lipitension"), are associated with a high risk of cardiovascular events. In clinical practice, it is not just the age itself that is important, but the presence of geriatric syndromes in patients. In particular, frailty is characterized by a high risk of adverse outcomes and death, as well as loss of autonomy. This article presents current data on the efficacy and safety of antihypertensive and lipidlowering therapy in elderly patients. It also discusses the thesis that fixed-dose combination of amlodipine, perindopril and atorvastatin can increase adherence to therapy and ensure a balance between the efficacy and safety of treatment in elderly comorbid patients with a number of geriatric syndromes. The treatment of such patients is traditionally associated with polypharmacy and uncontrolled use of medications.